1992
DOI: 10.1620/tjem.166.395
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Radiation Therapy Combined with Hyperthermia against Pancreatic Carcinoma.

Abstract: Fourteen patients with pancreatic carcinoma were treated by intraoperative radiation therapy (TORT) combined with hyperthermia (hyperthermia group). Their treatment results were compared with those of fifty five patients treated by TORT without hyperthermia (control group). Most of patients underwent some kind of chemotherapy for the carcinoma and some of them received post-operative irradiation. Although there was no significant difference in pain relief between hyperthermia group and control group, the local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 6 publications
(10 reference statements)
2
17
0
Order By: Relevance
“…After the first and second selection (Figure 1), 14 studies were included [53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Two patient cohorts were each described in two articles; for these we excluded the oldest [67,68] and included the latest [54,57].…”
Section: Literature Searchmentioning
confidence: 99%
See 3 more Smart Citations
“…After the first and second selection (Figure 1), 14 studies were included [53][54][55][56][57][58][59][60][61][62][63][64][65][66]. Two patient cohorts were each described in two articles; for these we excluded the oldest [67,68] and included the latest [54,57].…”
Section: Literature Searchmentioning
confidence: 99%
“…The included 14 studies combined 395 pancreatic cancer patients of whom 248 received HT (Table 1). Six out of 14 studies used a control population that enabled a comparison between treatments with and without hyperthermia [54,55,57,60,62,66]. In two studies, patients with a variety of carcinomas were included, but data were reported for the pancreatic patients separately [53,59].…”
Section: Literature Searchmentioning
confidence: 99%
See 2 more Smart Citations
“…Criticism 20 years ago was regarding the apparent inability to sufficiently generate surface heat [5]. A Greek group published promising data about unresectable palliative cases with a scheme of multi-schedule chemotherapy combined with radiation (45 Gy) plus a single session of hyperthermia during bypass surgery [6].…”
Section: Intraoperative Superficial Heatingmentioning
confidence: 99%